2011
DOI: 10.1177/183335831104000103
|View full text |Cite
|
Sign up to set email alerts
|

Professional Practice and Innovation: The Coding Masterpiece: A Framework for the Formal Pathways and Processes of Health Classification

Abstract: This article empirically defines the formal pathways and processes that enable and frame hospital clinical classification in an activity-based funding environment. These structured actions include: learning and training; abstracting; clinical knowledge locating and confirming; coder-doctor communication; coder-coder communication; the complicated sub-set of code searching and decision-making processes that constitute practical clinical 'coding'; allocation to diagnosis-related groups; confirmation of financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The value of performing internal audits (within the hospital) was discussed often (Cheng et al, 2009; Bramley and Reid, 2005b; Gentul and Davis, 2011: 31; Price and Robinson, 2011; Santos et al, 2008; Uzkuraitis et al, 2010). Cheng et al (2009) reported a blind re-coding audit of 752 surgical cases that showed 16% of the cases changed DRG which equated to a revenue increase of more than A$575,000.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of performing internal audits (within the hospital) was discussed often (Cheng et al, 2009; Bramley and Reid, 2005b; Gentul and Davis, 2011: 31; Price and Robinson, 2011; Santos et al, 2008; Uzkuraitis et al, 2010). Cheng et al (2009) reported a blind re-coding audit of 752 surgical cases that showed 16% of the cases changed DRG which equated to a revenue increase of more than A$575,000.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the potential financial impact, auditing the work of others is useful for developing several skills in CCs. During an internal audit, the CC can learn patience, gain an understanding of others’ thought processes, and experience what is needed to gather evidence and present feedback to another CC that justifies the recommended coding change (Price and Robinson, 2011). External audits provide good feedback to CCs about their coding practices if the audit is managed well, with an emphasis on education (Price and Robinson, 2011; Reid, 2013: 238; Shepheard and Moore, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that clerical workers are better at coding than clinical staff, and that partnerships between clinicians and coders improves accuracy (4,12). The appointment of a dedicated OMFS procedural coder for a short time on the OMFS ward after the first review aimed to provide coders a better insight into OMFS procedures and facilitate better communication with clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…While the systems discussed, a radio frequency identification-based electronic medical record system and a medical record scanning project, are quite different, they both have potential to change the way health information management work is carried out and therefore will impact on traditional HR and IR policies. (Price & Robinson 2011) have contributed a delightful piece that perfectly describes the complexity of the work of clinical coders, and highlights the importance of carefully managing this particular human resource. Conditions of employment and workplace arrangements must stay abreast of the needs of this group of people as the role of the clinical coder becomes increasingly important under the proposed activity-based funding (ABF) system.…”
Section: Industrial Relations and Human Resources: Management Challenmentioning
confidence: 99%